1989
DOI: 10.1136/gut.30.9.1206
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter associated gastritis in patients with non-ulcer dyspepsia: a double blind placebo controlled trial with colloidal bismuth subcitrate.

Abstract: SUMMARY Fifty consecutive patients with non-ulcer dyspepsia and a Campylobacter associated gastritis (CAG) were randomly assigned to treatment with colloidal bismuth subcitrate (CBS) 240 mg twice daily or placebo, according to a double blind study design. After the blind treatment an 'open' treatment with CBS was started in both groups. Twenty six patients treated with CBS showed a significant reduction in colonisation with Campylobacter pyloni and a significant improvement in the Whitehead gastritis score. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
5

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(26 citation statements)
references
References 16 publications
(3 reference statements)
0
21
0
5
Order By: Relevance
“…Superior results were reported after treatment with a combination of two or more antibiotic drugs, especially after triple therapy including, e.g., metronidazole, amoxicillin, and bismuth subcitrate (3). Except for treatment of duodenal ulcer disease that had been resistant to conventional therapy, the risks of possible toxicity, side effects, and development of bacterial drug resistance do not justify the widespread use of antibiotic combinations for relatively harmless conditions such as antral gastritis, especially since there controversy about the clinical relevance of gastritis in nonulcer dyspepsia remains (10,14,17,26).…”
Section: Resultsmentioning
confidence: 99%
“…Superior results were reported after treatment with a combination of two or more antibiotic drugs, especially after triple therapy including, e.g., metronidazole, amoxicillin, and bismuth subcitrate (3). Except for treatment of duodenal ulcer disease that had been resistant to conventional therapy, the risks of possible toxicity, side effects, and development of bacterial drug resistance do not justify the widespread use of antibiotic combinations for relatively harmless conditions such as antral gastritis, especially since there controversy about the clinical relevance of gastritis in nonulcer dyspepsia remains (10,14,17,26).…”
Section: Resultsmentioning
confidence: 99%
“…[186][187][188][189][190][191][192] All reported global dyspepsia symptom scores. The majority of the trials evaluating bismuth assessed the role of H. pylori eradication in NUD.…”
Section: Bismuth Saltsmentioning
confidence: 99%
“…Two trials included both H. pylori-positive and -negative individuals and these groups were entered separately to evaluate any difference in outcome according to infection status. 191,192 Six trials reported global dyspepsia improvement as a dichotomous outcome [187][188][189][190]192 and there was a trend towards bismuth salts being more effective than placebo, although this was of marginal statistical significance (RR reduction, 40%; 95% CI, -3 to 65) (Figure 10). Again, significant heterogeneity was noted in the analysis (Q = 18.31; df = 5; p = 0.003), due to the inclusion of one trial 190 with a very low placebo response rate (5%) and a correspondingly large treatment effect (RR reduction, 79%).…”
mentioning
confidence: 99%
“…density in antral biopsies though gastritis did not resolve completely in the patients stud ied here except 1. Whether persistence of other factors perpetuating gastritis as sug gested recently [35] or minute amounts of H.p. undetected by histology prevent com plete healing of gastritis is unclear.…”
Section: Discussionmentioning
confidence: 99%